The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s10863-018-9747-y
|View full text |Cite
|
Sign up to set email alerts
|

Cross regulation between mTOR signaling and O-GlcNAcylation

Abstract: The hexosamine biosynthetic pathway (HBP) integrates glucose, amino acids, fatty acids and nucleotides metabolisms for uridine diphosphate N-acetylglucosamine (UDP-GlcNAc) synthesis. UDP-GlcNAc is the nucleotide sugar donor for O-linked β-N-acetylglucosaminylation (O-GlcNAcylation) processes. O-GlcNAc transferase (OGT) is the enzyme which transfers the N-acetylglucosamine (O-GlcNAc) residue onto target proteins. Several studies previously showed that glucose metabolism dysregulations associated with obesity, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…Since it was observed that pharmacological inhibition of mTOR enhances proteasomal and autophagic degradation of OGT in HepG2 cells ( 34 ). We have also demonstrated that inhibition of mTOR affects OGT protein level and overall O -GlcNAcylation levels in HCT116 colon cancer cell line ( 35 ). In breast cancer cell lines the positive regulation of OGT expression through mTOR is dependent on c-Myc-induced heat shock protein 90A (HSP90A) transcription ( 36 ).…”
Section: O -Glcnacylation and Pi3k/akt/mtor Signaling Pathwamentioning
confidence: 83%
See 1 more Smart Citation
“…Since it was observed that pharmacological inhibition of mTOR enhances proteasomal and autophagic degradation of OGT in HepG2 cells ( 34 ). We have also demonstrated that inhibition of mTOR affects OGT protein level and overall O -GlcNAcylation levels in HCT116 colon cancer cell line ( 35 ). In breast cancer cell lines the positive regulation of OGT expression through mTOR is dependent on c-Myc-induced heat shock protein 90A (HSP90A) transcription ( 36 ).…”
Section: O -Glcnacylation and Pi3k/akt/mtor Signaling Pathwamentioning
confidence: 83%
“…Finally, it was shown that O -GlcNAcylation regulates the mitogenic mTOR signaling pathway through targeting the mTOR inhibitor AMPK ( 35 , 52 , 53 ). Increased O -GlcNAcylation in colon cancer cells, either by OGT overexpression or OGA inhibition, reduces phosphorylation of AMPK at Thr172, activates mTOR and induces cell growth in vitro in LoVo cell line and in vivo in LoVo cell-derived tumors of BALB/c-nu/nu mice ( 52 ).…”
Section: O -Glcnacylation and Pi3k/akt/mtor Signaling Pathwamentioning
confidence: 99%
“…Obesity is another area of research that has revealed a dynamic between mTOR and O-GlcNAc. When analyzing normal mice and Ob/Ob type mice, there were increased levels of OGT expression and mTOR phosphorylation ( 56 ). A corresponding in vitro experiment using colon cancer cells also demonstrated higher OGT expression and phosphorylated mTOR, as well as higher levels of O-GlcNAcylation.…”
Section: Sustained O-glcnacylation Correlates With Increased Phosphormentioning
confidence: 99%
“…A corresponding in vitro experiment using colon cancer cells also demonstrated higher OGT expression and phosphorylated mTOR, as well as higher levels of O-GlcNAcylation. Treatment of these cell lines with an mTOR activator (MHY1485) showed a slight increase in phosphorylated mTOR, OGT, and O-GlcNAcylation and a significant amplification in phosphorylated p70S6K ( 56 ). On the other hand, treatment with an mTOR inhibitor, rapamycin, caused distinct decreases in phosphorylated mTOR, OGT, O-GlcNAcylation and complete inhibition of p70S6K phosphorylation ( 56 ).…”
Section: Sustained O-glcnacylation Correlates With Increased Phosphormentioning
confidence: 99%
“…Several proteins which regulate macrophage function, i.e. Akt/mTOR, HIFa, as well as the NFκB and NFAT families [35,[45][46][47], were shown to be O-…”
Section: Discussionmentioning
confidence: 99%